Sufi articulations of civility, globality, and sovereignty. Issue 2 (4th May 2018) - Salvatore, Armando
Abstract: This article provides an analysis of Sufi life and organization, combining historical depth and theoretical awareness. It investigates how Sufism emerged as an urban phenomenon. Sufi brotherhoods were at the forefront of a proto-globalization based on a hemisphere-wide networking between metropolitan regions, rural provinces, and nomadic formations. Furthermore, cities became nodes within wider circulations, rather than, as in European and Weberian models, centers of corporate powers. The emerging patterns of civility were open-ended, balancing inner cultivation, communicative skills, and outward etiquette. The article shows how this global civility translated into original conceptions of sovereignty that were more malleable than those of the European Leviathan. A millenarian universalism imbued with Sufi saintliness bolstered the centralized sovereignty of early modern Muslim empires. Sufi contributions to these empires nurtured a cosmopolitan culture, facilitating commercial exchange and intellectual connectedness between Europe and China. When Europe rose to global hegemony, neo-Sufi movements engaged in state-building processes which challenged European colonial presence. The article concludes by exploring how post-Sufi developments within Muslim-majority postcolonial societies re-oriented state power and led to the emergence of a trans-territorial notion of sovereignty.